Muon-spin-relaxation studies of magnetic order and dynamics of the n = 2 Ruddlesden-Popper phases Sr2RMn2O7 (R = Pr, Nd, Sm, Eu, Gd, Tb, Dy, and Ho) - Bewley, R; Blundell, S; Lovett, B; Jestadt, T; Pratt, F; Chow, K; Hayes, W; Battle, P; Green, M; Millburn, J; Rosseinsky, M; Spring, L; et al. (1999)
Zero field muon spin relaxation (μSR) has been used to study the magnetic properties of n=2 Ruddlesden-Popper phases Sr2RMn2O7, where R = Pr, Nd, Sm, Eu, Gd, Tb, Dy, and Ho. The results show that the size of the lanthanide ion is crucial in determining the magnetic state and dynamics of the system. Because muons are implanted throughout the bulk of the sample, impurity phases contribute only according to their volume fraction. Hence in the case of biphasic samples the data are dominated by the majority phase. Although none of our samples has a ferromagnetic ground state, colossal magnetoresistance (CMR) is observed over a wide temperature range, 4 K